Norma de gênero e uso de drogas: normalização e diferença na experiência de mulheres - Isabela Saraiva de Queiroz (2015)
In this thesis we investigate the drug use by women under the heterossexual gender norm and its effects in the way how health care is organized in this field. In order to attain the proposed objective, initially we performed a systematic bibliography review of studies about female drug users, produced in Brazil in the last 30 years (from 1984 to 2013), trying to identify the way scientific discourses elaborated this experience. The sample is composed by studies indexed in the following databases: SciELO, BDTD, LILACS, Portal Domínio Público and Portal de Periódicos da CAPES. Overall, we catalogued 142 works - 93 papers, 38 Masters dissertations and 11 Doctoral thesis -, 81% of them from the Health area. The bibliographical review indicated a progressive increase in the usage of the category gender in the writings about the theme. However, the analyzed works do not use gender as a theoretical organizer and restrict themselves to the analysis of biological sex differentiation aspects. We identified few qualitative studies, with relation to the analysis of the narratives of women about themselves and their experiences with drugs, as opposed to the notable presence of quantitative studies, focused on the identification of the women profiles, usage patterns and damage estimation. We concluded that scientific studies about the theme place women primarily in the private and subjective phenomena fields, contributing to the production and maintenance of gender inequalities. In the second stage of the thesis we tried to analyze theoretically the constitution of the heterosexual gender norm itself, as well its normalization devices, based on the theoretical contributions from Judith Butler and Michel Foucault. Thereafter, in an attempt of going forward beyond the limits of production of discourses about drugs made by experts, we tried, in a third stage of the thesis, to listen to the women themselves, as legitimate enunciators of their experiences. For this purpose, we realized a multi-sited ethnography, starting from the hearing of a group of women inserted in a public mental health care system and then immersing ourselves in the daily lives of three of them, following the women through the spaces where they circulated: shelter, school, health care facility, and also their own homes and neighborhoods. Hearing the women represented the meeting with the production of differences, disarticulating fixed meanings and challenging the orientational matrix of intelligibility of the professional practices directed to them. The interpellation resulting from this meeting indicated possibilities of drug experiences unknown until then, and only understood in a partial and incipient manner, because they, among other things, undermine the ideals of hegemonic normalization. Finally, we suggested a few guidelines to women drug users health care, specially related to the importance of bonding and intimate relationship for a professional performance offering services capable of sustaining the monitoring of singular ways of engaging the world, as well as collaborating in the enhancement of preservation strategies in the drug usage.